Existing otherwise: from Jean-Paul Sartre and Maurice Merleau-Ponty to a critical phenomenology of bodily otherness - Hughes, AG (2022)
With their existential phenomenologies, Jean-Paul Sartre and Maurice Merleau-Ponty insisted upon a radical new conception of consciousness as embodied, in the world, and among other subjects. Their L’Être et le néant and the Phénoménologie de la perception have made perhaps the most lasting impression of any modern intellectual tradition on theories of the body and the social world, in philosophy as in the human sciences, in France as elsewhere. They have proven uniquely valuable for critical theorists of race, gender, sexuality, disability, and illness looking to give accounts of the lived experience of ‘bodily otherness’. In their will to rework French existential phenomenology to take stock of othering, violence, and oppression, accounts of this kind point at once to its shortcomings and its promise as a framework for making sense of such experiences. This thesis seeks to explore the depth of those shortcomings, in the first place, and the scope of that promise, in the second. Opening with a discussion of ‘bodily otherness’ and a comparative appraisal of Sartre and Merleau-Ponty’s theories of the body and autrui, it moves through to critique their engagements with othering and oppression, positing that those engagements are circumscribed by a normativity that operates at the most basic level of their thought to foreclose the realisation of the very ideals that they themselves place at the heart of phenomenology. The thesis thus contends that existential phenomenology might yet illuminate the lived experiences of ‘others’, should it remain alive to, and refuse complicity with, its own normative biases. It closes by taking up that mantle, reading Sartre and Merleau-Ponty with and against one another to propose some elements of a critical phenomenology of ‘bodily otherness’, and to stress the imperative of empathy as a philosophical and political practice.